Sporothrix Schenckii: a rare fungal lesion mimicking common granulomas, a case report - ., Niranjanakesav; Bama, Sathiya; ., Radhakrishnan; Kumar, Arbind (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
The patient, a 35-year-old lady, reported for a deeply fixed skin swelling in the leg. The proper diagnosis is likely to be missed if attention is concentrated only on the granulomas. Though diagnosis is possible through Hand E stains, accurate identification of the characteristic morphological features of this fungus is essential for proper diagnosis and treatment. Contrary to the usually held view, in this patient, unusually large number of fungal elements with varying morphology is noticed in Hand E sections.